Interactive Effects of Procedural Justice and Outcome Negativity on Victims and Survivors of Job Loss - Brockner, Joel; Konovsky, Mary A.; Cooper-Schneider, Rochelle; Folger, Robert; Martin, Christopher; Bies, Robert J. (Academy of Management Journal, 1994)
Three studies respectively explored the interactive effects of procedural justice and outcome negativity on the victims of job layoffs, on survivors, and on lame ducks, employees who knew they would soon be laid off. Consistent results emerged for all three types. When procedural justice was perceived to be low, individuals reacted more adversely to the extent that outcomes were perceived to be negative. When individuals felt that procedural justice was relatively high, however, perceived outcome negativity was not related to their reactions.